Multifunctional MXene/C Aerogels for Enhanced Microwave Absorption and Thermal Insulation - Wu, Fushuo; Hu, Peiying; Hu, Feiyue; Tian, Zhihua; Tang, Jingwen; Zhang, Peigen; Pan, Long; Barsoum, Michel W.; Cai, Longzhu; Sun, ZhengMing (Nano-Micro Letters, 2023)
Two-dimensional transition metal carbides and nitrides (MXene) have emerged as promising candidates for microwave absorption (MA) materials. However, they also have some drawbacks, such as poor impedance matching, high self-stacking tendency, and high density. To tackle these challenges, MXene nanosheets were incorporated into polyacrylonitrile (PAN) nanofibers and subsequently assembled into a three-dimensional (3D) network structure through PAN carbonization, yielding MXene/C aerogels. The 3D network effectively extends the path of microcurrent transmission, leading to enhanced conductive loss of electromagnetic (EM) waves. Moreover, the aerogel’s rich pore structure significantly improves the impedance matching while effectively reducing the density of the MXene-based absorbers. EM parameter analysis shows that the MXene/C aerogels exhibit a minimum reflection loss (RLmin) value of − 53.02 dB (f = 4.44 GHz, t = 3.8 mm), and an effective absorption bandwidth (EAB) of 5.3 GHz (t = 2.4 mm, 7.44–12.72 GHz). Radar cross-sectional (RCS) simulations were employed to assess the radar stealth effect of the aerogels, revealing that the maximum RCS reduction value of the perfect electric conductor covered by the MXene/C aerogel reaches 12.02 dB m2. In addition to the MA performance, the MXene/C aerogel also demonstrates good thermal insulation performance, and a 5-mm-thick aerogel can generate a temperature gradient of over 30 °C at 82 °C. This study provides a feasible design approach for creating lightweight, efficient, and multifunctional MXene-based MA materials. Highlights: 1 Curving 2D MXene into 1D nanofibers can effectively stop the restacking of MXene flakes, and then the nanofibers are used to construct a lightweight and multifunctional MXene/C aerogel. 2 The MXene/C aerogels achieved an RLmin of − 53.02 dB and EAB of 5.3 GHz. The radar cross-sectional reduction value of MXene/C aerogels can reach 12.02 dB m2. 3 Integrating multiple functions such as thermal insulation, sensing, and microwave absorption into one material—MXene/C aerogel.